Para além das sete tradições da teoria da comunicação: Entrevista com Robert T. Craig - Craig, Robert; Daros, Otávio (Questões Transversais, 2022)
One of the most renowned scholars of communicational thinking, Robert T. Craig talks about the contributions that have marked his trajectory in the academic field of communication. His main propositions concern the constitutive metamodel of communication theory and philosophy of communication as a practical discipline. The North American author also explains his understanding of communication as a universal and culturally variable phenomenon, calling attention to the potential for developing theoretical traditions rooted in non-Western cultures.